Altitude decreases time trial performance - Daley, P.; Martin, D.; Roberts, A.; Hahn, A.; Gore, C.; Spence, R. (1998)
Australian male cross country ski team members (n = 9, 19.78 ± 2.5 yr, 76.63 ± 6.4 kg, 184.8 ± 4.9 cm) completed a multistaged, discontinuous maximal exercise test and a 45 minute simulated time trial performance using a treadmill pole striding technique. Testing occurred in a chamber which was supplied with either an oxygen enriched gas mixture (sea level conditions - 149 mmHg PO2) or a nitrogen enriched gas mixture (1800 m conditions - 132 mmHg PO2). Oxygen uptake (ml.kg-1.min-1), heart rate (bpm), blood oxygen saturation (%) and PO2 were all significantly lower at altitude than at sea level during the three time trial laps. T